KANITA International Conference On Gender Studies (KICGS 2018) - Press for Change: Re-imagining & Co-creating Women’s Empowerment - Azmi, Zaireeni (KANITA, 2018)
Women’s empowerment includes both personal strenghthening and enhancing women’s potential at a personal and societal level. Women ‘s empowerment is basically enhancing women’s life chances. As such, my conceptual understanding is that Women and Empowerment is how women’s choices and decisions direct their lives into private or public spheres of activity. Also that women’s empowerment can be illustrated based upon a life history . Within that context, I will share my personal journey towards the experience of empowerment. In particular to illustrate about women and empowerment within the context of my activities and professional role in a changing society like Indonesia. Also that womens’ empowerment as an activity is about a perception that what women do with their lives is based upon an individual decision, forced or as a free choice. But that in the final analysis what women do with their lives should remain an individual decision. As an individual decision, it becomes a responsibility to realize that choice. I also underline the importance that urging women to assist each other in accomplishing an aspired goal is important in women’s empowerment.